APLIKASI SISTEM KEAMANAN BASIS DATA DENGAN TEKNIK KRIPTOGRAFI RC4 STREAM CIPHER - Jumrin Jumrin; Sutardi Sutardi; Subardin Subardin (Informatics Engineering Department of Halu Oleo University, 2016)
Database security is a very important aspect in an information system. A specific information is generally addressed to specific group. Therefore it is an important matter for a company to prevent information leak from a database so that the information contained in it does not fall to unauthorized party. Cryptography is an alternate solution that can be used to secure a database. One method that can be used to secure a database is by using encryption. The method used to secure a database is the RC4 Stream Cipher encryption because the method has advantages in processing speed and high security level. By using Stream Cipher encryption method to secure a database, the information contained in it can only be accessed by authorized party. RC4 (Rivest code) Stream Cipher method is one of symmetric key algorithm in form of Stream Cipher that process unit or data input, message, or information. Research results show that a data in a database table can be encypted. The encryption and decryption process are faster and have high security level. Keywords— Cryptography, RC4 Stream Cipher, Encryption, Decryption